Service-Oriented Architecture Application in Long-Term Care Institution: A Case Study on an Information System Project Based on the Whole Person Concept in Taiwan - Chung, Feng-I; Lo, Chia Lun (International Journal of Computing Sciences Research; Vol 1 No 3 (2017): Vol 1, No 3, 2018)
Purpose – The caring approach for long-term care is different with the general care because it emphasizes comprehensive health care. If the system establishment lacks integrated concepts, the system will then be unsuitable. This study aims to develop an innovative system project based on the whole person concept and provides the experience for applying the concept of Service-Oriented Architecture (SOA) to integrate different operations of the system which called U-care project.   Method – This involves substituting the function module of the original system architecture with a service-based approach to provide a service interface. In addition, there must be a connection between the well-defined interface for the services and the formation of comprehensively integrated system architecture. Evaluations were conducted both on the programmers of the U-care project and on end user experience form using the system. Results – The results describe our resulting functional design of the system. The implanted experience based on SOA was also presented and the services were success practice in a long term care institution. Conclusion – The contribution of this paper is the project functional design and practical feasibility. It also showed the SOA platform with a set of reusable domain function service is suitable for the long term care institution. It can support the actual improvement on the project development schedule and operational performance of personnel. Recommendations – Further work on emphasizing the establishment of domain knowledge by developers when developing long-term care related software to reduce difficulties in communication with users, refining the process applied to the SOA is recommended to improve the efficiency of the project. Research Implications – Service-oriented computing promotes the approach of assembling application components into a network of services that can be loosely coupled to create flexible, dynamic business processes and agile applications. Therefore, the architecture of service oriented uses services to support development teams can achieve rapid, low cost, interoperable, evolvable and massively distributed long term care system.